Toll-like receptor 4 confers inflammatory response to Suilysin - Bi, Lili; Pian, Yaya; Chen, Shaolong; Ren, Zhiqiang; Liu, Peng; Lv, Qingyu; Zhen, Yuling; Hao, Huaijie; Yuan, Yuan; Jiang, Yongqiang (Frontiers in Microbiology, 2015)
Streptococcus suis serotype 2 (SS2) is an emerging human pathogen worldwide. A large outbreak emerged in the summer of 2005 in China. Serum samples from this outbreak revealed that main proinflammatory cytokines were significantly higher in patients with streptococcal toxic-shock-like syndrome (STSLS) than in patients with meningitis only. However, the mechanism of the cytokine storm in SS2 caused STSLS remained unclear. In this study, we found that SLY is the main protein inflammatory stimulus of SS2, and the native SLY (nSLY) stimulated cytokines independently of its hemolytic ability. Interestingly, a small amount of SLY (Å Mol/L) induced strong, long-term TNF-α release from human PBMCs. We also found that nSLY stimulated TNF-α in wild-type macrophages but not in macrophages from mice that carried a spontaneous mutation in TLR4 (P712H). We demonstrated for the ﬁrst time that SLY triggers the immune cells through TLR4. Additionally, Myd88 adaptor-p38-MAPK pathway was involved in this process. The present study suggested that the TLR4-dependent inflammatory response of host induced by SLY might be contributing to the STSLS caused by SS2 and p38-MAPK could be used as a target to control TNF-α over releasing induced by SS2.